Endoscopic ultrasound-guided ethanol ablation of a large metastatic carcinoid tumor: success with a note of caution - Mathers, Bradley W.; Harvey, Harold A.; Dye, Charles E.; Dougherty-Hamod, Brandy; Moyer, Matthew T. (Endoscopy International Open, 2014)
Endoscopic ultrasonography with fine needle infusion (EUS-FNI) of alcohol is the most reported method for EUS-guided tumor ablation. Several studies have reported successful EUS-guided ablation of pancreatic neuroendocrine tumors. However, these tumors have been relatively small (< 3 cm). In this report, a 50-year-old man with a metastatic carcinoid tumor with a large porta hepatis mass was referred to our clinic for EUS-guided ethanol ablation. After two separate EUS-FNI ablations, there was a 36 % reduction in tumor size (9.0 × 11.4 cm to 6.7 × 9.8 cm) with associated tumor lysis syndrome. Chromogranin A levels decreased from 460 to 132 ng/mL. The patient reported complete resolution of abdominal pain within 2 weeks, but only mild improvement in flushing and diarrhea. In conclusion, large metastatic neuroendocrine tumors can be successfully treated with EUS-guided ethanol ablation. Evidence-based guidelines are needed with regard to the appropriate volume of ethanol injected in EUS-guided ablation to promote the efficacy and safety of this emerging procedure.